Urgensi Pengawasan Pimpinan Terhadap Kinerja Pegawai Di Era Otonomi Daerah - Taufiq, Muchamad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
It was about ten years ago, Eldersveld and Derksen put forward their criticism which says : our knowledge of the nature of local political leadership in modern democracies based on systematic comparative scholarship is limited. This makes it difficult to generalize across political systems. Political scientists just have been more interested in their own political system, and in interviewing national poticians than in comparative studies of local leaders (1995:1). In many sense, Eldersveld and Derksen’s criticism is still relevant now days, and this book is partly aimed to fulfil that of the gap in scholarly literatures concerning Indonesian local leaders’ orientation towards decentralization and regional autonomy policies.